Delayed neurotoxicity in HER2-positive breast cancer: a case series on combined SRS and T-DM1 treatment - Turna, Menekse; Çağlar, Hale Başak (Frontiers in Oncology, 2024)
This case series presents four instances of late neurotoxicity observed in HER2-positive breast cancer patients with brain metastases following treatment with stereotactic radiosurgery (SRS) and subsequent trastuzumab emtansine (T-DM1) therapy. Despite initial control of intracranial disease, patients experienced neurological deterioration months to years post-treatment. Radiological assessments revealed distinct patterns consistent with radiation necrosis, particularly in areas previously treated with SRS and subsequent T-DM1 administration. These changes, characterized by enlarging cystic masses with hemorrhagic components, emphasize the importance of vigilant monitoring in patients undergoing combined SRS and T-DM1 therapy for brain metastatic breast cancer. This report underscores the need for further investigation into the long-term effects of combining SRS with novel systemic therapies, particularly in HER2-positive breast cancer patients with brain metastases. Understanding and mitigating late neurotoxicity are critical for optimizing treatment strategies and improving patient outcomes.